Impacts of Ocean Acidification on Reproduction and Early Life Development in Marine Teleost Fish—A Synthesis - Rebecca J. Bridge; Benjamin T. McClelland; Silvana N. R. Birchenough; Martina H. Stiasny (Fish and Fisheries, 2026)
Ocean acidification (OA) remains a major and underexplored threat to marine fishes, particularly regarding reproductive physiology and early life stages (ELS). Although research over the past 15 years has documented diverse OA effects, substantial knowledge gaps persist. Most studies focussed on a limited set of species from North America and Europe, leaving broad uncertainty across phylogenetic groups, geographic regions and multi‐stressor conditions. In adult fish, especially females, elevated p CO 2 can shift energy allocation to prioritise reproductive output at the expense of egg or clutch size. While adult and juvenile fish have well‐developed acid–base balancing systems, embryos and larvae possess only rudimentary mechanisms, making them more vulnerable to OA. This article stresses the importance of understanding these physiological and mechanistic responses to predict the future of fish stocks and ecosystem health as OA intensifies due to ongoing CO 2 emissions. Our results highlight that OA responses in fish are highly variable and often specific to life stage and species, with acute and sometimes stage‐specific effects not fully documented. Lastly, our recommendations on targeted research and funding are necessary to address the remaining knowledge gaps, including broadening taxonomic and geographic sampling, exploring multi‐stressor scenarios and improving understanding of the downstream effects of OA on fish reproduction and development. Maintaining robust fish populations is vital for food security, employment and ecosystem functioning, making continued investigation into OA's impacts a scientific and societal priority.